Pemanfaatan Media Realia Dengan Program Pembelajaran Indvidual Pada Aspek Keterampilan Sosial Anak ASD Usia Dini - Sagala, Anita Chandra Dewi; Sulianto, Joko; Selliawati, Atiek (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Abstract Social skills are crucial for early childhood development, especially for children with ASD. Success in improving social skills in children with special needs depends heavily on the learning system implemented. Based on observations, Fun & Play Inclusive Kindergarten Semarang implements an individual learning program utilizing realia media to develop the social skills of children with special needs. This study aims to determine how the use of realia media in an individual learning program can support social skills in early childhood with autism. This study used a qualitative research study with a descriptive qualitative approach. The results showed that the use of realia media is adjusted to the severity of autism, ranging from mild, moderate, to severe, where each level has different social skill abilities. The success of this learning method is influenced by several factors such as the suitability of the media to the learning objectives, teacher competence, the child's physical and emotional condition, cooperation between parents and teachers, and the appropriate implementation of special dietary patterns for children. It is hoped that this research will further enrich teachers' knowledge in the world of inclusive education and improve their readiness to become an inclusive school that can open opportunities for anyone to receive adequate educational services.